Analysis of complex problem-solving skills using vr-based interactive media through an ethnopedagogy approach - Nurannisa, Andi; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Iqbal Akbar; Yulita, Yulita (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Complex Problem Solving is one of the essential skills needed to navigate the workforce. However, students' mastery of Complex Problem Solving remains relatively low, particularly in mathematics. This study is a quantitative research aimed at analyzing Complex Problem Solving skills using interactive teaching media based on virtual reality through an ethnopedagogy approach. The research was conducted at UPT SMP Negeri 1 Kahu by dividing the trial classes into limited trials, extensive trials, and experimental trials.To assess Complex Problem Solving skills, five essay questions were used, reflecting indicators such as identifying complex problems, evaluating/analyzing problem information, and generating problem-solving solutions. The results showed that the average Complex Problem Solving skills of students in the trial classes increased by 87%. Meanwhile, in the control class, students' learning outcomes only improved by approximately 62%. These findings indicate that using interactive learning media based on virtual reality through an ethnopedagogy approach effectively enhances students' Complex Problem Solving skills.